Single-dose levamisole at breeding alters early pregnancy immune-endocrine profiles without affecting fertility in ewes - Risvanli, Ali; Kholmurzaevich, Abdugani Abdurasulov; Sharabidinovich, Kursantbek Attokurov; Mamatkalykovych, Pirimkul Mamatkalykov; Duyshobayeva, Aiturgan; Obdunov, Elmurat; Tynaibekovna, Rosa Abdyldaeva (Bmc, 2025)
Background Reproductive efficiency in sheep is influenced by complex interactions between the endocrine and immune systems, particularly during early pregnancy. Immunomodulators such as levamisole are known to enhance immune responses and have been investigated for their potential to improve reproductive outcomes in various animal species. However, the effects of levamisole administered at the time of breeding on both pregnancy rates and key immunoendocrine markers in ewes remain unclear. This study aimed to evaluate the effects of levamisole, administered at varying doses during breeding, on pregnancy rates and selected immune and endocrine parameters in ewes. A total of 30 ewes were randomly assigned to three groups (n = 10 each): a control group received subcutaneous saline; the second group received levamisole at 2.5 mg/kg; and the third group received 7.5 mg/kg, all administered at the time of breeding. Blood samples were collected on days 0, 10, and 20 post-breeding. Levels of IFN-gamma, IL-2, TNF-alpha, progesterone, activin A, activin B, follistatin, and total immunoglobulin (Ig) were measured using commercial ELISA kits. Results Pregnancy rates did not differ statistically between the groups (p > 0.05). However, on day 10, pregnant ewes in the 2.5 mg/kg group showed significantly higher activin A levels (p < 0.05). Activin B levels were elevated in pregnant ewes in both the control group (day 10) and the 7.5 mg/kg group (day 20) (p < 0.05). Follistatin levels were higher on day 10 in pregnant control animals (p < 0.05). IFN-gamma and IL-2 levels increased in pregnant animals, particularly in control and 7.5 mg/kg groups, respectively. Progesterone levels peaked on day 10 in all groups. Conclusions While the measured immune and endocrine parameters varied, these changes did not impact the pregnancy rates.
Keywords: Activin; Cytokine; Ewe; Follistatin; levamisole